Archeological Survey and Site Assessment at Great Basin National Park - Wells, Susan J. (the Digital Archaeological Record)
Archeological survey and site assessment at Great Basin National Park were conducted in June and July of 1989 by archeologists from the Western Archeological and Conservation Center. Developed and proposed development areas totalling 780 acres were systematically surveyed and 11 prehistoric archeological sites were recorded in the alluvial fan that extends from the park entrance to Lower Lehman Campground. Thirteen previously known prehistoric sites and one newly discovered site were recorded at various locations throughout the park as part of the site assessment. Sixteen historic period properties were visited and recorded. Prehistoric sites date to Archaic, Fremont and Shoshone periods and include artifact scatters, rock art sites and caves. The historic period sites are related to mining. ranching. the tourist industry associated with Lehman Caves, mapping and logging. The archeological significance of all sites recorded by this project is summarized and recommendations are made for the management of significant archeological resources. The contributions of this research to the prehistory and history of the park and Snake Valley are considered.